Morphological Characterization of Leaf and Flower of Local Sweet Potato [Ipomea batatas L.] From Agam and Solok District, West Sumatra Province - Sumilah Sumilah; Nirmala F. Devy; Hardiyanto Hardiyanto (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumberdaya Genetik Pertanian, 2019)
The diversity of sweet potatoes from Agam and Solok District of West Sumatra is known to be very high, it causes somedifficulties in taxonomic research. The diversity analysis based on the leaf and flower morphology has not done before in local sweet potato from Agam and Solok District. The purpose of this study was to determine the diversity of local varieties of sweet potato from West Sumatra based on leaves and flowers morphological characters. The analysis was conducted on 21 accessions collected from West Sumatra regencies and germplasm collection. The Morphological characterization was done based on CIP/AVRDC/IBPGR descriptor list. The data of morphological character was analyzed using Primary Component Analysis (PCA) and grouping analysis using Cluster Analysis through SAHN method on NTSys program, with UPGMA as similarities criteria. The results showed that the first four principal components contributed 89.6% to the plant diversity. The sweet potatoes were divided into 2 clusters, with the main distinguishing character was the existence of plant flowers. Information on genetic diversity and the pattern of relations between accessions will be very useful for the West Sumatra people in developing superior sweet potatoes.